Transdisciplinarity: Marginal Direction or Global Approach of Contemporary Science? - Mokiy, Vladimir; Lukyanova, Tatiana (Informing science, 2021)
Aim/Purpose: The article is designed to contradict the existing opinion that “transdisciplinarity is a marginal direction of contemporary science.” Background: The difficulties of implementing transdisciplinarity into science and education are connected with the fact that its generally accepted definition, identification characteristics, and methodological features are still missing. In order to eliminate these disadvantages of transdisciplinarity, its prime cause and initial idea had to be detected. Then an attempt was made to analyze correspondence of the existing opinions about transdisciplinarity with the content of its prime cause and initial ideas. Methodology: The bibliometric content analysis of the literature reviews on the subject of transdisciplinary was used in order to determine correspondence of the opinions about transdisciplinarity with the meaning of its prime cause and initial ideas, as well as to generalize these opinions. This method allowed detecting and classifying opinions into 11 groups including 39 stereotypes of transdisciplinarity. For substantiation of transdisciplinary approaches consistency with the approaches of the contemporary science C.F. Gauss random variables normal distribution was used. The “Gauss curve” helped to show the place of transdisciplinary and systems transdisciplinary approaches in the structure of academic and systems approaches. The “Gauss curve” demonstrated the step-by-step broadening of the scientific worldview horizon due to sequential intensification of synthesis, integration, unification, and generalization of the disciplinary knowledge. Contribution: Based on rethinking the results from bibliometric content analysis of the literature reviews, the generalized definition of transdisciplinarity could be formulated, as well as the definition for the transdisciplinary and systems transdisciplinary approaches could be given. It was shown that transdisciplinarity is a natural stage for development of contemporary science and education, and the transdisciplinary approaches were capable to suggest the methods and tools to solve the complex and poorly structured problems of science and society. Findings: Many existing stereotypes of transdisciplinarity do not meet its prime cause and initial ideas. Such stereotypes do not have deep philosophic and theoretical substantiation, as well as not suggesting the transdisciplinary methods and tools. Thus, the authors of such stereotypes often claim them to be transdisciplinary or suggest perceiving them as transdisciplinarity. This circumstance contributed to the fact that many disciplinary scientists, practitioners, and initiators of higher education view transdisciplinarity as a marginal direction of contemporary science. Based on the generalized definition of transdisciplinarity, as well as its prime cause and initial ideas, we managed to show that transdisciplinarity is presented in contemporary science in the form of two different approaches: the transdisciplinary approach and the systems transdisciplinary approaches. The objective of the transdisciplinary approach is ensuring science development at the stage of synthesis and integration of disciplinary knowledge. The objective of the systems transdisciplinary approach is ensuring solving of modern society problems using unification and generalization of disciplinary knowledge. Recommendation for Researchers: The researchers should consider that within the limits of the transdisciplinary approach the disciplinary specialists are managed. Within the limits of the systems transdisciplinary approach the disciplinary knowledge is managed. Thus, the transdisciplinary approach is efficient for organization and research with participation of the scientists of complementary disciplines. An example for such research can be a team of researchers of medical disciplines and complimentary disciplines from chemistry, physics, and engineering. The systems transdisciplinary approach is efficient for organization and performance of research with participation of scientists of non-complementary disciplines, for example, economics, physics, meteorology, chemistry, ecology, geology, and sociology. Future Research: In terms of the main initial idea, transdisciplinarity is formed as a global approach. The global approach should have a traditional institutional form: it should be a science discipline (meta-discipline) and have carriers with the transdisciplinary worldview. Training for such carriers can be organized by the universities within the limits of the systems transdisciplinarity departments and Centers of Systems Transdisciplinary Retraining for Disciplinary Specialists. Thus, it is reasonable to initiate discussion for the idea to reform the disciplinary structure of the universities considering creation of such departments and centers.